Analysis of Roman Inggarden in Joko Pinurbo's Cyber Literature as Teaching Material for Writing Contextual-Based Poetry - Andriyana Andriyana (The University of Kuningan, 2022)
Literature is inseparable from society in the process of its creation and content. The well-known opinion of Welek and Warren literary works is the social documentation that occurs in society. The form of social documentation in poetry was also carried out by Joko Pinurbo who wrote poems during the pandemic in cyber literature written in Republika and Detik. This study aims to uncover the value of contextuality with Roman Inggarden's theory and its relevance as teaching material for writing contextual-based poetry (CTL). This research uses a qualitative descriptive method with research steps (1) Looking for Joko Pinurbo's poems in the Mass Media (2) Compiling data, and (3) Data analysis based on theory (4) Linking the analysis results with their relevance to teaching materials. In the analysis of Roman Inggarden's poem written by Joko Piburbo, it can be illustrated by the analysis that the poem discusses covid-19 that occurs in social society. This is a form of contextuality that proves that the poem is related to learning to write CTL-based poetry.